Urgency of Indonesian Waters Area Protection from Illegal Unreported Unregulated Fishing - F.P, Ramadhan Marco; L.N.A, Mutiara Firsty; A., Sutan Syahnendra (Journal of ASEAN Dynamics and Beyond, 2020)
Indonesia as the largest archipelagic country has considerable potential with vast areas of water that can be utilized, but it must be accompanied by strict supervision because of many illegal practices such as IUU Fishing. This problem becomes important to deal with because Indonesia's maritime potential cannot be maximized as long as IUU Fishing practices remain. The author(s) formulated a problem in the form of "How does protect Indonesian waters against the practice of IUU Fishing?" The author(s) uses a qualitative descriptive method to analyze the problem of how IUU Fishing can be handled in Indonesian waters. The theory used is the Collective Security proposed by A.F.K Organski. In this paper, we argued that there must be decisive action to stop the activities of IUU Fishing and the government is expected to immediately pay attention to the importance of protecting Indonesian territorial waters from lurking hazards. Not only the danger of smuggling of goods and other information but also, activities such as violating ship crossings culminating in illegal fishing. It must be dealt with a strong legal basis so that in the future, it will become a warning for other countries that Indonesia is serious in safeguarding its sovereignty